Heliconical cholesteric liquid crystals as electrically tunable optical filters in notch and bandpass configurations. Issue 11 (2nd September 2021) - Nava, G.; Ciciulla, F.; Simoni, F.; Iadlovska, O.; Lavrentovich, O. D.; Lucchetti, Liana
ABSTRACT: Heliconical cholesteric liquid crystals are a recently proposed novel class of liquid crystalline materials in which the chiral pitch can be tuned by an external electric field acting parallel to the helical axis. Here we show that these materials can be used as tunable optical filters of a simple architecture. The spectral properties of transmitted light can be tuned within the whole visible range. In particular, the bandpass wavelength can be shifted from 405 nm to 637 nm by changing the applied field from 2.7 to 1.7 V/µm. The electric field can also switch the filters on and off, within 1 s or less. Moreover, the filters work with both polarised and unpolarised light and can be switched from a notch to a bandpass configuration by changing the polarisation of incident light. An optical switch among three different laser lines is also reported as an additional possible application. Graphical Abstract: uf0001